Challenges encountered with argatroban anticoagulation during cardiopulmonary bypass - Shvetank Agarwal; Beth Ullom; Yasser Al-Baghdadi; Michael Okumura (Wolters Kluwer Medknow Publications, 2012)
Use of argatroban as an alternative to heparin during cardiopulmonary bypass (CPB) in patients with heparin-induced thrombocytopenia has gained some attention in the past two decades. Dosing of argatroban during CPB is complex due to lack of complete understanding of its pharmacokinetic profile and the various elements during CPB that may alter its plasma levels. We report a case where the challenges in dosing argatroban led to failure to provide adequate anticoagulation during CPB, as evidenced by clot formation in the oxygenator, and extensive bleeding in the postoperative period.